The Application of Buddhamma Principle in solution Gambling of community in Phrae Province. - Sricompa, Raweerose; Intem, Nawatro (Journal of International Buddhist Studies, 2016)
This research is interested in special study about gambling because this thing can be saw clearly. Although it has law measure and campaign from Buddhism and other organization but the gambling is still have in the community. In the dimension of Phrae community is not worse all around province. It was found that it had some community where had become self-immunity by using people participation system of Sangha, rural leader and people in the community for making the best life of the family without part of ruin. Therefore, the researcher team investigated the application of Buddhadhamma principle in solution gambling of community in Phrae Province for seeking the example community that has behavior by bringing the Buddhadhamma to apply in this problem. The main objectives of this research were 1) to study the Buddhadhamma principle in solution the path to ruin, 2) to study the application of the Buddhadhamma principle in solution the gambling of community in Phrae Province and also 3) to study the guidelines in solution the gambling in according with Buddhadhamma principle in community of Phrae Province. The findings are discussed in four issues related to the application of Buddhamma principle in solution gambling of community in Phrae Province 1. From the general data of interviewer. Most of the persons are layman, age between 41-60, female gender, high school degree, work for wages occupation.Most of the status in community are the temple committee. 2. There are doctrines that can solve the path of ruin namely; the virtues that protect the world 2, root of good actions 3, craving 3, contentment 3, fourfold division of money, house-life happiness 4, virtues conductive to benefits in the present 4, benefits which one should get from wealth 5, and treefold training. 3. The application of Buddhamma principle in solution the gambling of community in Phrae Province has applied the threefold trainingas precept, meditation, and wisdom. Part of the role of leader as Buddhist monks, community leader in the community are conducted the various activities in community namely; 1) The subjects who have played important role for solving the solution of gambling’s in the community namely; abbot, leader of family, and leader in community by establishing in format of the community committee for watch out the problem of gambling playing in community or village. 2) It has area for using the center in stopped the gambling in community namely; temple, school, learning center in community, funeral, and the various festivals. 3) It has important network that is made the community free from gambling namely; temple, village, school, people, media, community development, leader in village, community police, the network of Thai Cultural community loving project, municipality, Tumbol Administrative Organization, and public section. Moreover, There are the activities for campaigning the free from gambling in the community namely, meeting the countryperson, settling the rule in meeting, have coordination with police man for searching information together, listening the Dharma Teaching at temple, chanting, exercise, playing music, training, the vocation, practicing meditation, and doing the account current, A/C 4. There are 5 methods in solution the gambling of community in Phrae Province in according with Buddhadhamma principle namely; 1) Bringing the threefold training to practice in the life way for wellbeing. 2) The Leader is not lead and acted in gambling playing. 3) The Buddhist monk must train the people to have the moral and the threefold training by giving the suggestion about the danger of gambling playing. 4) Admiring the example person in the life way that is free from the path of ruin. 5) Instilling the conscious to the people stopped the gambling playing by themselves permanently. The solution the gambling by a whole namely; 1) Setting the ruler of law for using in the community. 2)Helping take care people in community and suggestion the people to know that how do the damages of the gambling. 3)Training about the danger of gambling to the youth and people for understanding. 4)Stopping the person who lives outdoors to play the gambling in community and having the suppressive measure absolutely when has disobeyed. 5)Using the threefold training for solving the problem about the gambling by organizing the good activity in community and emphasizing the more people participation. In addition, the problem and obstacle should emend side by side by using many ways namely; Instilling and supporting from the leader and Buddhist Organization solving by themselves, using the rule of law.